Pengaruh Kepercayaan dan Kepuasan Terhadap Loyalitas Nasabah Mitra Beasiswa AJB Bumiputera 1912 Cabang Kota Pariaman - Wardi, Yunia; Mesta, Hendri Andi; Rahmayeni, Ilda (Jurnal Kajian Manajemen Bisnis, 2017)
This research is aimto analyze the influence of trust and satisfaction on customer loyalty of Mitra Beasiswa AJB Bumiputera 1912 of Pariaman. The population in this research is the Mitra Beasiswa AJB Bumiputera 1912 of Pariaman in 2015. The sample was taken by purposive sampling using the formula of Slovin, with sample size as much as 90 respondents. Data analysis is performed multiple regression analysis and hypothesis testing using F test and t-test. The results of this study show that trust and satisfaction have a significant effect on customer loyalty of Mitra Beasiswa AJB Bumiputera 1912 of Pariaman.